Species of Terebellides (Polychaeta, Terebellidae, Trichobranchinae) from the Brazilian coast. - Garraffoni, André R.S.; Lana, Paulo C. (Iheringia. Série Zoologia, 2003)
Terebellides sepultura sp. nov. is described from the continental shelf bottoms off southern Brazil. Terebellides carmenensis Solis-Weiss, Fauchald & Blankensteyn, 1991 is newly recorded for the Brazilian coast and notes on T. anguicomus F. Müller, 1858 and T. klemani Kinberg, 1867 are provided. A key to 28 species of Terebellides is given.
World Polychaeta Database (WPolyDb)